Patterns and Characteristics of Poisoning in Patients Admitted to a Peripheral Tertiary Care Hospital in Eastern India: A Record-based Observational Study - Rajat K Goswami; Shambo S Samajdar; Shatavisa Mukherjee (Bengal Physician Journal)
Background: Poisoning represents a significant public health concern globally, with varying epidemiology based on regional socioeconomic conditions, cultural practices, and healthcare accessibility. This study aimed to elucidate the patterns, demographics, and outcomes of different types of poisoning in a peripheral tertiary care hospital in India. Materials and methods: A retrospective, record-based observational study was conducted over 12 months, including 66 patients with poisoning, excluding drug abuse, insect, and snakebites. Demographics and clinical data were analyzed using SPSS, and confidentiality was maintained in line with ethical standards. Results: The study found a female predominance in poisoning cases (77%), with a mean patient age of 28.2 years. Organophosphate (OP) poisoning was most common (45.45%), followed by kerosene (10.47%) and unidentified drug poisoning (9.30%). The overall mortality was 10.6 and 7.5% of patients were referred to a higher-level center for advanced care. Conclusion: The prevalence of OP and kerosene poisoning underscores the need for increased public awareness and improved storage and handling practices. The higher incidence among females and significant referral rates to Tertiary Care Centers indicate a need for targeted preventive strategies and improved primary care management.